An understanding of water governance systems in responding to extreme droughts in the Vietnamese Mekong Delta. Issue 2 (4th March 2021) - Nguyen, Minh N.; Nguyen, Phuong T. B.; Van, Tri P. D.; Phan, Vu H.; Nguyen, Binh T.; Pham, Vu T.; Nguyen, Trung H.
ABSTRACT: In 2016, extreme drought and saline intrusion led to widespread damage and livelihood disruption for many people in the coastal region of the Vietnamese Mekong Delta. Through an integrated multi-step approach of literature and stakeholder analysis, focus group discussions and interviews with local governments and farmers, an understanding of the local water governance systems and their functioning is gained, providing insight into the power, interest and responsibility of multiple agencies. Development of more responsive and inclusive water governance systems, with improved early warnings and information flows during extreme events, is needed to improve the resilience and adaptation of the region.